Strong metal–support interactions impart activity in the oxygen reduction reaction: Au monolayer on Mo2C (MXene). (2nd November 2018) - Cheng, Cheng; Zhang, Xilin; Fu, Zhaoming; Yang, Zongxian
Abstract: The rational design of low-cost, high-efficiency, corrosion-resistant and persistent-activity oxygen reduction reaction (ORR) electrocatalysts is a common goal for the large-scale application of fuel cells. Inspired by the excellent characteristics of MXenes when used as substrate materials and recent experiments of depositing metal nanoparticles on MXenes, we systematically investigated monolayer metal thin films decorated by Mo2 C (MXene) (MML /Mo2 C, M = Cu, Pd, Pt, Ag and Au) as ORR catalysts using density functional theory. According to the stability and adsorption properties, we speculate that AuML /Mo2 C possesses outstanding ORR performance and enhanced durability in comparison with Pt/C catalysts. The ORR on AuML /Mo2 C proceeds through a four-electron reduction pathway with comparable or even better activity than Pt(1 0 0), Pt(1 1 1) and commercial Pt/C catalysts both kinetically and thermodynamically. Strong metal–support interactions give rise to larger electronic perturbations in the supported Au monolayer in contact with Mo2 C, which strengthen the adsorption of oxygen-containing species and enhance the catalytic activity. Our current results indicate that AuML /Mo2 C is a promising ORR catalyst candidate to replace precious Pt/C catalysts due to its good stability, enhanced durability, low cost and high activity. We hope our results will inspire more experimental and theoretical research to further design, explore and apply advanced metal monolayer-supported MXene composites.